Dysfunctional mechanisms of adaptations a result of pathological relationships between daughter and mother - Sichkar, H. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article raises the question of women’s dysfunctional mechanisms of adaptation as a consequence of pathological relationships with the mother. Particular attention is paid to such of them: interpersonal dependence, depression, anxiety, frustration, aggression, rigidity. The Hirschfeld Interpersonal Dependency Inventory, the Zung Self-Rating Depression Scale and the Eysenck Personality Questionnaire were used for an empirical study. In order to achieve these goals, a sample of 40 women aged 20 to 25 years was formed. A sample of this age allows you to look at a woman as an already established personality, and highlights the trends and characteristics of her interactions with others. The result of the study proved that the representatives of single-parent families have a greater degree of severity for all the indicators were given (interpersonal dependence, depression, anxiety, frustration, aggression, rigidity). This means that the absence of a permanent mother’s partner (along with other factors covered in the article) catalyzes and promotes the process of forming the pathological relationship between a daughter and mother, which in turn becomes the basis for the formation of dysfunctional mechanisms of adaptation to the daughter as an expression of maternal injury. Maternal trauma or a mother complex is defined as the collective concept of a daughter and mother pathological relationship negative consequences. This is explained by the fact that the daughter in these conditions becomes the only one object of the projections of mother’s fears, desires and dissatisfied needs, besides, she becomes the only source of love. A harmonious relationship with the mother is the basis for a full-fledged personality formation, while a natural interaction violation in the form of a fierce struggle for similarity and difference leads to an inadequate perception of the world and oneself, which is transferred to all subsequent generations in a closed circle.